Avaliação do efeito da exposição ao cobre e diferentes cores de luz na composição bioquímica de Pediastrum sp - Neves, Camila de Almeida (Universidade Federal de São Carlos, 2023)
Microalgae are organisms with morphological and phylogenetic diversity, which also vary in their biochemical composition. This diversity confers its use in sectors of economic relevance, such as nutrition, pharmaceuticals and cosmetics. In general, optimal conditions for growth are employed, but the cultivation can be manipulated in terms of its physicochemical characteristics, such as micronutrients and light conditions, to alter the metabolic response of the alga with the consequent alteration in the production of biomolecules. This work aimed at investigating the effect of copper and different light colors on the growth and physiology of the microalgae Pediastrum sp., focusing on the production of biomolecules. The copper concentration used corresponded to the EC20, calculated through tests in a 96-well microplate with 30 concentrations ranging from 4.10-8 to 9.10-4 M nominal copper, with absorbance monitoring for 6 days. Once the concentration was defined (EC20, 7.5.10-7 M), the algal physiology experiment was carried out. The determination of biomolecules in the biomass was done in 96 h cultures, including the blue, red and white LEDs as variables. After this period, chlorophyll a, chlorophyll b, carotenoids, proteins and carbohydrates in the biomass were quantified. The results showed that blue light favoured the biosynthesis of carotenoids and carbohydrates and, in association with copper, significantly increased the concentration of chlorophylls. Copper at a concentration equivalent to EC20 influenced the photosynthetic process, increasing photochemical dissipation (qP) independent of light color, and non-photochemical dissipation (NPQ) for white and red lights. The results presented in this study contribute to the expansion of knowledge about the combination of copper and light colors in the physiology of the Chlorophyta Pediastrum sp., as well as in the production of biomolecules and microalgae biotechnology.
Evaluation of the effects of exposure to copper and different light colors on the biochemical composition of Pediastrum sp
Keywords: Biomoleculas; Biomolecules; Fotossíntese; Photosynthesis; Fisiologia; Physiology; CIENCIAS BIOLOGICAS::BOTANICA::BOTANICA APLICADA